Psychological Distress in Outpatients With Lymphoma During the COVID-19 Pandemic - Romito, Francesca; Dellino, Miriam; Loseto, Giacomo; Opinto, Giuseppina; Silvestris, Erica; Cormio, Claudia; Guarini, Attilio; Minoia, Carla (Frontiers in Oncology, 2020)
Cancer patients are a population at high risk of contracting COVID-19 infection, especially when undergoing immunosuppressive treatment, and also of developing severe complications due to the infection. On the meanwhile, they are forced to go to hospital to receive chemotherapy also during lockdown. In this context, we have evaluated the psychological status of onco-hematological outpatients receiving infusion and not deferrable anti-neoplastic treatment for lymphoproliferative neoplasms, with the aim of both measuring the levels of post-traumatic symptoms, depression and anxiety during the pandemic and also investigating the perception of risk of potential nosocomial infection. The Impact of Event Scale-Revised (IES-R) and the Hospital Anxiety and Depression Scale (HADS) were administered to all patients. Moreover, patients were investigated about their worries regarding the impact of COVID-19 on their lives as onco-hematologic patients. Since the 2nd to the 29th April 2020 (during the first phase of the lockdown period in Italy), seventy-seven outpatients were prospectively evaluated. They were diagnosed with non-Hodgkin's lymphomas, classical Hodgkin lymphoma and Chronic lymphocytic leukemia / Small lymphocytic lymphoma. Mean age was 56.6 (range 22-85). We found that 36% of patients had anxiety (HADS-A), 31% depression (HADS-D), and the 43% was above the cut-off for the HADS-General Scale; 36% fulfilled the diagnostic criteria for post-traumatic distress syndrome (PTDS). Women and younger patients were found more vulnerable to anxiety and PTSD. The study firstly analyse the psychological impact of COVID-19 pandemic on the frail population of patients affected by lymphoproliferative neoplasms, so underlying the importance of screening for the emotional and distress conditions and then offering a psychological support.